An overview of Eulerian CFD modeling and simulation of non-spherical biomass particles. (October 2019) - Ullah, Atta; Hong, Kun; Gao, Yanan; Gungor, Afsin; Zaman, Muhammad
Abstract: Recently, biomass has gained attention as a renewable energy resource due to low emissions and ample availability. Thermochemical conversion technologies to handle biomass are being developed rapidly. Due to complicated multiscale nature of biomass thermochemical conversion, numerical methods are playing important role in understanding detailed underlying mechanisms governing the processes. In this context, computational fluid dynamics (CFD) is playing an important role both as a research as well as design tool. There have been many publications in recent years using CFD to simulate systems involving biomass feedstock. In this work, we have tried to briefly summarize the CFD simulations of biomass systems especially after the year 2010 with focus on the drag models being used under the framework of Eulerian methodology. Drag modeling of biomass systems requires special attention due to non-spherical nature of particles both before the initiation of conversion process as well as during the process of thermochemical conversion. It is, therefore, this aspect that we have tried to highlight in this work with a brief review of recent relevant literature as well as a summary of some popular spherical and non-spherical drag models that can be or are being used to model systems containing biomass particles. Highlights: Eulerian CFD of hydrodynamics of non-spherical biomass particles is reviewed. Drag force models after 2010 for non-spherical particles are discussed. Existing gaps in research of biomass particles are identified. A multiscale modeling strategy is recommended for biomass particles.